Ferulic acid prevents lead‐induced testicular oxidative stress and suppressed spermatogenesis in rats. (10th March 2017) - Hasanein, P.; Fazeli, F.; Parviz, M.; Roghani, M.
Summary: Lead affects multiple organ systems including testis. We investigated the effects of ferulic acid (FA) on lead‐induced oxidative stress and spermatogenesis suppression in rats. Animals received lead acetate (500 mg/L in drinking water) and/or FA (50 mg/kg, i.g .) for eight weeks. Lead increased testicular malondialdehyde (MDA) and nitrite levels and decreased glutathione (GSH) content and catalase (CAT) activity. Lead decreased testis weight and testosterone level. Sperm parameters decreased in lead group. FA ameliorated the decreased testis weight, serum testosterone as well as sperm count, viability, motility and normal morphology in lead group. FA improved antioxidant capacity as well as sperm count, viability, motility and normal morphology. FA decreased Johnsen's mean testicular biopsy score (MTBS) criteria by restoring degeneration, atrophy and tubular disarrangement. FA also normalised spermatogonia, spermatocytes and spermatids numbers in lead group and led to increases in number of Leydig and Sertoli cells. FA showed beneficial effects in lead‐induced testicular oxidative stress and spermatological disorders, through inhibiting lipid peroxidation and enhancing antioxidant defence systems. The positive effects of FA on Leydig cells may be involved in restoring testosterone levels in lead group. FA can be considered a potential candidate to protect testis against the deleterious effect of lead intoxication.